Conexões e vínculos: um olhar sobre as redes comunicativas entre mulheres - Machado, Gabriela Pereira (2024)
Progredir Quarta Colônia Geopark, an extension program funded by the federal government and developed by the Federal University of Santa Maria (UFSM), between 2022 and 2023, offered short courses focusing on the tourist and cultural activity of the UNESCO Quarta Colônia World Geopark, in order to promote the professional qualification of people registered in the Single Registry, mainly women. The problem of this research addresses the effective existence of communicative networks, involving the connections and bonds of women participating in the Program. The general objective of this research, in this sense, is to analyze the existing communicative networks and how they are constructed among these women. To achieve this results, the specific objectives include mapping communication networks in the community, understanding the motivating factors for participation, investigating everyday communication processes and reflecting on the importance of these interaction spaces. The study is based on the need to understand the social and communicative dynamics of low-income women involved in the program. Using a qualitative approach with triangulation of techniques, the research is based on semi-structured interviews, participant observation and data analysis through action research methodology. Furthermore, it seeks to contribute to the academic field by exploring topics such as communication for development, communicative networks, communication and citizenship and gender and class relations. In the context of the final considerations of the study, the fundamental importance of understanding communication processes in the daily lives of women participating in the Progredir Program stands out. The study was guided by the central question about the effectiveness of communication networks in this specific context. The analysis revealed the presence of a dynamic and multifaceted communication network, which goes beyond the boundaries of the formal networks initially identified, permeating different spheres of the participants' lives, from moments in courses to informal interactions and events such as graduation. Data analysis allowed not only to verify the existence of communicative networks, but also to understand the complexity and nuances of these processes within the program. The support networks offered by the program play an important role in promoting these communication processes, facilitating not only participation in the courses, but also contributing to the establishment of significant emotional bonds between participants. However, even with the presence of these communication networks, the study identified a significant gap with regard to participants' knowledge and access to public policies and citizenship rights. This gap reveals a failure not only of the program, but also of public institutions in the region in addressing issues essential to the true emancipation of participating women.